Marco teórico de la propiedad fiduciaria - Yglesias Mora, Roberto (2015)
This paper defends the thesis that the trust property is a special property, which is accused the classic characteristics of the domain and new dynamics in their development, with the compression and decompression of its attributes. The existence of a fiduciary ownership is recognized from the point of view of rights in rem, and is not seen only as an accessory Trust governed by commercial law.